(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One of the leading methods of teaching mathematics is the method of mathematical modeling. The use of the modeling method allows us to show the versatility of the mathematical apparatus, it makes it possible to unify the description of processes that are diverse in nature. The use of concepts related to modeling, directly in the process of teaching mathematics, allows you to improve the methodology of teaching it, avoid a formal approach to teaching, and implement integration ties. Students develop ideas about the role of mathematical methods in transformative activities, about the nature of the reflection of the phenomena of the surrounding world by mathematics.